Effect of Ethanolic Leaf Extract of Azadirachta indica A. Juss (Neem) on Testicular Morphometry of New Zealand White Rabbits - Sharma, Pushkar; Singh, Bhoopendra; Srivastava, Sushant; Singh, Jaswant; Singh, Jitendra P.; Kumar, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Azadirachta indica (neem) is an ascent, evergreen medicinal plant native to Indian subcontinent and most of the African countries.Neem causes deleterious effects on the fertility of mammals and might be used to investigate its contraceptional use in stray animalpopulation. The aim of the study was to assess the effect of ethanolic leaf extract of A. indica on testicular morphometry (length, width,thickness and volume) and histology of male New Zealand White rabbits. Eighteen healthy, adult male rabbits, aged 12 months old,weighing between 1.83–1.90 kg were randomly divided into three groups, each group comprised of 6 animals. Group A was kept ascontrol with distilled water only, while Group B and C were given ethanolic leaf extract of A. indica @ 100 mg/kg and 200 mg/kg bodyweight/day for 60 days, respectively, in drinking distilled water. Testicular length, width and thickness of both testicles were measuredon day 0, 15, 30, 60 and 120 after initiation of treatments by Vernier calipers. Volume was also calculated by standard formula. The resultsrevealed significant decrease in morphometry of the testicles at day 60 over day 0 in treated groups, and it showed variable reversal innext 60 days after discontinuation of treatment.
Keywords: Azadirachta indica; Rabbits; Testicular morphometry